Analisis Renderfarm Menggunakan Teknologi Cloud Computing dengan Virtual Container Berbasis Docker: Studi Kasus InkubatorX - Fajar, Muhammad; Faizah, NM; Karo Karo, Panser (Jurnal Sistem Komputer (SISKOM), 2025)
The 3D animation industry continues to grow rapidly, but it is often hindered by the limitations of adequate computational resources. The rendering process, which converts 3D models into realistic images, requires significant computational power and often takes a long time. This study uses an experimental method to measure execution time during rendering with varying frame values. These variations are applied to each slave computer and compared to determine the speedup in execution time. Observations were made to understand the impact of changing frame values on rendering time. With the implementation of a render farm system, errors in the rendering process can automatically be re-submitted until completion, and utilizing multiple computational resources in parallel can speed up the rendering process. This makes the rendering process more efficient and helps complete animation projects more quickly. The system design process begins with a general observation, followed by software design, and concludes with the deployment of the render farm on the server. Parallel computer testing was carried out by synchronizing the time between the Master, Slave, and Client using network time protocols. The results of the tests indicate that the use of a render farm can significantly reduce rendering time, providing an efficient solution to overcome hardware limitations in 3D animation rendering.